Iban as a koine language in Sarawak - Shin, Chong (UI Scholars Hub, 2021)
This article attempts to delineate the issue of linguistic homogeny in Iban variants in Sarawak (Malaysia). In brief, the Iban speakers are claimed to descend from Upper Kapuas watershed, Western Kalimantan (Indonesia). Based on local traditions and oral materials, this ethnic group began to move out from Kapuas watershed and penetrate into Sarawak in sixteenth century. After several generations, they expanded to become the major ethnic group in the state. Several recent studies show that the number of ethnic Ibans in West Kalimantan is fairly small and the distribution of Iban communities often displays a pattern of distant pockets or enclaves. The purpose of this article is to explain how a minority group became a majority ethnic group in a newly settled territory. This article argues that this research question is strongly related to the ethnonym of “Iban” and regional dialect levelling or koineization. During the initial stage of the migration, the term “Iban” was an exonym. By the mid-twentieth century, the exonym “Iban” or “Sea Dayak” was gradually becoming an endonym. The change in the status of this ethnonym has enlarged the population size of the “Iban” in Sarawak. The existence of several Iban-like ethnic groups in Sarawak, for example, the Balau, Remun, Kantu’, Milikin, and Kumpang, adds support to this argument. This article revisits the issue of linguistic homogeny of the Iban language, taking the language koineization approach. A phonological analysis on the Ibanic varieties spoken in West Kalimantan offer a possible explanation that the Iban variants in Sarawak have appeared as a stable linguistic variety as a result of “dialect levelling” and “simplification”. Furthermore, the development of koine Iban seems to fulfil several features in the koine developmental continua proposed by J. Siegel (1985).